Enhancement of the Electrochemical Performance of LiNi1/3Co1/3Mn1/3O2 Cathode Material by Double-Layer Coating with Graphene Oxide and SnO2 for Lithium-Ion Batteries. (22nd April 2019) - Ma, Yuxin; Cui, Ping; Zhan, Dan; Gan, Bing; Ma, Youliang; Liang, Ying
Abstract : The graphene oxide-coated SnO2 -Li1/3 Co1/3 Mn1/3 O2 (GO-SnO2 -NCM) cathode material was successfully synthesized via a facile wet chemical method. The pristine NCM and GO-SnO2 -NCM were characterized by X-ray diffraction, scanning electron microscopy, energy-dispersive spectroscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The results showed that the double-coating layer did not destroy the NCM crystal structure, with multiple nano-SnO2 particles and GO uniformly covering the NCM surface. Electrochemical tests indicated that GO-SnO2 -NCM exhibited excellent cycling performance, with 90.7% capacity retention at 1 C after 100 cycles, which was higher than 74.3% for the pristine NCM at the same cycle. The rate capability showed that the double-coating layer enhanced surface electronic–ionic transport. Electrochemical impedance spectroscopy results confirmed that the GO-SnO2 -coating layer effectively suppressed the increased electrode polarization and charge transfer resistance during cycling.